Structure of the bluetongue virus capsid - Verwoerd, D W; Els, H J; De Villiers, E M; Huismans, H (Journal of virology, 1972)
Seven polypeptides were found to be present in the capsid of the bluetongue virus (BTV), four of which are major and three are minor components. This number and size distribution is the same as that found in reovirus, which has a similar segmented, double-stranded ribonucleic acid genome. In both viruses an excellent correlation is found between the molecular weights of certain genome segments and those of the polypeptides, suggesting a direct coding relationship between them. Careful comparison, however, indicates that the correlation patterns of the two viruses are different, suggesting that different genome segments may be utilized to code for certain capsid proteins. This phenomenon may be related to the fact that these viruses can be distinguished morphologically, reovirus having a larger diameter and possessing a double-layered capsid against the smaller single capsid of the BTV. Utilizing the degrading effect of CsCl gradients, it was demonstrated, however, that two of the BTV polypeptides are present as a diffuse protein layer surrounding the capsid. This outer layer probably has some of the functions of the reovirus outer capsid, one being the "masking" of a viral transcriptase which could be demonstrated after its removal.